Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Direktorat Jendral Mineral Dan Batu Bara - Juliana, Rini; Murniyati, Murniyati (CV Warnak Johanna Nusantara, 2026)
Abstracts - This research is motivated by the importance of employee performance in achieving organizational goals, which are influenced by various internal factors, especially leadership style and work motivation. This study aims to analyze the influence of leadership style and work motivation on employee performance at the Directorate General of Minerals and Coal. The research method used is a quantitative method with a descriptive approach. The population in this study were all 40 employees of the Directorate General of Minerals and Coal, with a saturated sampling method. Data collection was carried out through questionnaires, observations, interviews. There were several tests carried out, namely data quality tests, classical assumption tests, hypothesis tests, determinant coefficient tests, T tests (partial), and F tests (simultaneous). The results of the study showed that partially the Leadership Style (X1) was known to have a calculated t value of 1.147 with a level of 0.05 smaller than 5%. This calculated t value was greater than the t table, which was 2.026 and Work Motivation (X2) had a positive and significant effect on employee performance. Simultaneously, these two variables also significantly influence employee performance. The F-test results obtained a calculated F-value of 198.299, contributing 91.4%, while the remainder was influenced by other variables outside this study. This finding indicates that improving good leadership style and high work motivation can optimally improve employee performance. In conclusion, the variables of the Influence of Leadership Style (X1) and Work Motivation (X2) simultaneously have an effect on Employee Performance (Y). Keywords: Leadership Style, Motivation, Employee Performance Abstracts - This research is motivated by the importance of employee performance in achieving organizational goals, which are influenced by various internal factors, especially leadership style and work motivation. This study aims to analyze the influence of leadership style and work motivation on employee performance at the Directorate General of Minerals and Coal. The research method used is a quantitative method with a descriptive approach. The population in this study were all 40 employees of the Directorate General of Minerals and Coal, with a saturated sampling method. Data collection was carried out through questionnaires, observations, interviews. There were several tests carried out, namely data quality tests, classical assumption tests, hypothesis tests, determinant coefficient tests, T tests (partial), and F tests (simultaneous). The results of the study showed that partially the Leadership Style (X1) was known to have a calculated t value of 1.147 with a level of 0.05 smaller than 5%. This calculated t value was greater than the t table, which was 2.026 and Work Motivation (X2) had a positive and significant effect on employee performance. Simultaneously, these two variables also significantly influence employee performance. The F-test results obtained a calculated F-value of 198.299, contributing 91.4%, while the remainder was influenced by other variables outside this study. This finding indicates that improving good leadership style and high work motivation can optimally improve employee performance. In conclusion, the variables of the Influence of Leadership Style (X1) and Work Motivation (X2) simultaneously have an effect on Employee Performance (Y). Keywords: Leadership Style, Motivation, Employee Performance